2022
DOI: 10.1002/tox.23699
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin attenuates inflammatory response in allergic rhinitis mice by inhibiting the TLR4/MyD88/NF‐κB signaling pathway

Abstract: Background: Allergic rhinitis (AR) is an immunoglobulin E (IgE)-mediated immune inflammatory response that mainly affects the nasal mucosa. Currently, there is evidence that apigenin, as a flavonoid, has anti-allergic potential. Material/Methods: In vitro, compound 48/80 and lipopolysaccharide (LPS) were used to induce mast cell activation and inflammation in HMC-1 cells. In vivo, ovalbumin (OVA) induced and stimulated AR in BALB/c mice. ELISA was used to detect the contents of β-hexosaminidase, histamine, eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In AR, histamine plays an important part in itching, sneezing, and nasal congestion ( Yokota et al, 2015 ). After allergen excitation in the nose, the histamine level is increased in the nasal lavage of allergic individuals compared with that of non-allergic individuals ( Li et al, 2023 ). CAVO lowered the serum histamine level in rats with OVA-induced AR, alike that seen with the positive control (loratadine).…”
Section: Discussionmentioning
confidence: 99%
“…In AR, histamine plays an important part in itching, sneezing, and nasal congestion ( Yokota et al, 2015 ). After allergen excitation in the nose, the histamine level is increased in the nasal lavage of allergic individuals compared with that of non-allergic individuals ( Li et al, 2023 ). CAVO lowered the serum histamine level in rats with OVA-induced AR, alike that seen with the positive control (loratadine).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin meaningfully suppressed the production of these inflammatory cytokines compared to the LPS group [ 52 ]. A study result demonstrated that administration with apigenin increased Th1 cytokine and transcription factor levels and decreased Th2 cytokine and transcription factor levels and promoted the ratio of Th1/Th2 cells in allergic rhinitis mice [ 53 ]. The objective of the study was to investigate the anti-inflammatory effects of apigenin to evaluate its potential as an anti-psoriatic agent.…”
Section: Exploring the Pharmacological Potential Of Apigenin Through ...mentioning
confidence: 99%
“…Li et al. ( 112 ) showed that apigenin could attenuate the inflammatory response in AR through the TLR4/MyD88/NF-κB signaling pathway. Liu et al.…”
Section: Tlr4/irak4/nf-κb Signaling Pathway and Armentioning
confidence: 99%